On the Issue of “White Spots” in the History of Russian Philosophy (on the Example of the Philosophical Creativity by K.N. Leontiev) - Frolova, N.A. (Opción, 2019)
This article analyses two critical phenomena in the history of Russian philosophical thought of the 19th century: Slavophilism and the concept of soil to identify the possibility or impossibility of their identification. Through contextual and historical-philosophical analysis as a method, the author demonstrates that the tradition of Slavophilism continued to exist in the second half of the 19th century. In conclusion, Russian philosophy has deep-seated internal patterns that manifest themselves throughout its development, organically going back to the peculiarities of the national spiritual and material culture, mentality, geographical and climatic conditions of existence